2001
DOI: 10.1103/physrevb.64.212508
|View full text |Cite
|
Sign up to set email alerts
|

Fermi surface of the heavy-fermion superconductorCeCoIn5:The de Haas–van Alphen effect in the normal state

Abstract: Measurements of the de Haas-van Alphen effect in the normal state of the heavy-fermion superconductor CeCoIn 5 have been carried out using a torque cantilever at temperatures ranging from 20 to 500 mK and in fields up to 18 T. Angular-dependent measurements of the extremal Fermi surface areas reveal a more extreme two-dimensional sheet than is found in either CeRhIn 5 or CeIrIn 5 . The effective masses of the measured frequencies range from 9 to 20m*/m 0 .

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
103
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 124 publications
(118 citation statements)
references
References 5 publications
15
103
0
Order By: Relevance
“…T max is found to increase with increasing x, suggesting that the energy scale of the coherent heavy-fermion state becomes large with doping Ni. The increase in T max is similar to those observed in Snand Pt-doped CeCoIn 5 , but different from the decrease in T max found in the Cd, Hg, and Zn substitutions. 29,32,35) These opposite variations would mainly be attributed to the sign of the doped charge carrier in these compounds, as pointed out previously.…”
Section: Methodssupporting
confidence: 51%
See 4 more Smart Citations
“…T max is found to increase with increasing x, suggesting that the energy scale of the coherent heavy-fermion state becomes large with doping Ni. The increase in T max is similar to those observed in Snand Pt-doped CeCoIn 5 , but different from the decrease in T max found in the Cd, Hg, and Zn substitutions. 29,32,35) These opposite variations would mainly be attributed to the sign of the doped charge carrier in these compounds, as pointed out previously.…”
Section: Methodssupporting
confidence: 51%
“…At this critical Sn concentration, the NFL behavior is realized at zero magnetic field, correspond-ing to the T -linear dependence in electrical resistivity and the − ln T divergence in specific heat divided by temperature. The similarity of the NFL behaviors between CeCo(In,Sn) 5 and pure CeCoIn 5 indicates that the AFM quantum critical fluctuation is still enhanced in CeCo(In,Sn) 5 , whereas no AFM ordering is observed in a wide Sn concentration range. Furthermore, it is suggested that these features would be related to the two-dimensional nature, since the X-ray absorption study revealed that most of the doped Sn ions occupy the CeIn layer located at the tetragonal basal plane.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations